Advances in Grid-Connected Photovoltaic Power Conversion Systems - Yang, Yongheng; Kim, Katherine A.; Blaabjerg, Frede; Sangwongwanich, Ariya (Woodhead Publishing in energy., 2019)
Advances in Grid-Connected Photovoltaic Power Conversion Systems addresses the technological challenges of fluctuating and unreliable power supply in grid-connected photovoltaic (PV) systems to help students, researchers, and engineers work toward more PV installations in the grid to make society more sustainable and reliable while complying with grid regulations. The authors combine their extensive knowledge and experience in this book to address both the basics of the power electronic converter technology and the advances of such practical electric power conversion systems. This book includes extensive, step-by-step practical application examples to assist students and engineers to better understand the role of power electronics in modern PV applications and solve the practical issues in grid-connected PV systems.